2017
DOI: 10.1007/s12232-017-0277-4
|View full text |Cite
|
Sign up to set email alerts
|

Eudaimonic well-being, inequality, and health: Recent findings and future directions

Abstract: The theoretical and philosophical underpinnings of a eudaimonic model of well-being are examined and its empirical translation into distinct dimensions of well-being is described. Empirical findings have documented aging declines in eudaimonic well-being, but there is considerable variability within age groups. Among older adults who remain purposefully engaged, health benefits (reduced morbidity, extended longevity) have been documented. Eudaimonic well-being also appears to offer a protective buffer against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
0
28

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 74 publications
(79 reference statements)
8
157
0
28
Order By: Relevance
“…MWB is central to effective human functioning (Ryan & Deci, 2001;Ryff, 2017) and entrepreneurs are no exception. 'Happy' entrepreneurs are more likely to persist and perform better (e.g., Wincent, Örtqvist, & Drnovsek, 2008).…”
Section: Entrepreneurs' Mental Health and Well-being: A Review And Rementioning
confidence: 99%
“…MWB is central to effective human functioning (Ryan & Deci, 2001;Ryff, 2017) and entrepreneurs are no exception. 'Happy' entrepreneurs are more likely to persist and perform better (e.g., Wincent, Örtqvist, & Drnovsek, 2008).…”
Section: Entrepreneurs' Mental Health and Well-being: A Review And Rementioning
confidence: 99%
“…Experts argue that a large group of shareholders has more influence and control over the managers' activities, which in turn increases the value of the firms [68]. Over the past decade, institutional investors have become vital to improved performance with active monitors, and they have also been instrumental in increasing the value of shareholders by attracting more investments [69]. According to these arguments, several studies have found a positive and significant influence of active institutional shareholders on equity performance.…”
Section: Institutional Investorsmentioning
confidence: 99%
“…Drawing on humanistic and human development theories Carol Ryff [9] defined a comprehensive model of eudaimonic well-being which includes six dimensions: Having a positive evaluation of oneself and one's past (self-acceptance), having quality relationships with others (positive relations with others), continued growth, development and expansion of potential (personal growth), the belief that one's goals are purposeful and meaningful (purpose in life), the ability to effectively and competently manage one's life (environmental mastery), and finally, a sense of being self-determining, independent and regulating behavior from within (autonomy) [9]. This conceptualization, and the related scales, has been used widely in empirical studies-with a number of consolidations made by the author [42,43], but has made limited inroads into organizational studies.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%